Peripheral Isolates as Sources of Adaptive Diversity under Climate Change - Macdonald, Stewart L.; Llewelyn, John; Moritz, Craig; Phillips, Ben L. (Frontiers in Ecology and Evolution, 2017)
As climate change progresses, there is increasing focus on the possibility of using targeted gene flow (the movement of pre-adapted individuals into declining populations) as a management tool. Targeted gene flow is a relatively cheap, low-risk management option and will almost certainly come into increased use over the coming decades. Before such action can be taken, however, we need to know where to find pre-adapted individuals. We argue that, for many species, the obvious place to look for this diversity is in peripheral isolates: isolated populations at the current edges of a species’ range. Both evolutionary and ecological considerations suggest that the bulk of a species’ adaptive variation may be contained in the total set of these peripheral isolates. Moreover, by exploring both evolutionary and ecological perspectives it becomes clear that we should be able to assess the potential value of each isolate using remotely sensed data and three measurable axes of variation in patch traits: population size, connectivity, and climatic environment. Locating the “sweet spot” in this trait space, however, remains a challenge. Throughout, we illustrate these ideas using Australia’s Wet Tropics rainforests as a model system.